O pioneirismo em Santa Sariana – PR: uma proposta de análise das relações patriarcais - Vitorini, Rosilene Alves da Silva (2025)
The research shows the relationship between patriarchy and pioneering of the colonizer and lists some of its main problems, divided into two categories: related to the production of memories and historical discourses and those linked to the transmission of these memories to new generations. One of these issues is the tendency to value the pioneering that characterizes a process of emphasis on certain subjects and/ or social groups. Another equally urgent issue is the invisibility of the contributions of women who have promoted the construction of urban and rural space. Erasure observed both in official documents of the community, as in the school system of the municipality. The objective of this research is to understand the relationship between patriarchy and pioneering from the historical formation of the municipality of Santa Mariana - PR, based on the analysis of official historical documents and dialogical reflection with women of the locality. In this context, a list of aspects that allow a tension on the formative and contradictory structures of patriarchy and pioneering/ colonizer: the first refers to the understanding of the "naturalized" functions of historically excluded groups, as the women of the municipality. The second aspect of the research proposes to demonstrate how the patriarchy and the pioneering are evidenced in historical documents. The third aspect promotes a space for reflection, through interaction in an extensionist practice allied to research. The method used was the historical-dialectical materialism, trying to understand the operation of history from the real conditions of production of existence and significant materialities and the methodology effective the collection of data through bibliographical and documentary research, analysis of theoretical sources available in this subject, documents made available by institutions of the municipality of Santa Mariana, such as the city hall and municipal library, in addition to collecting additional information from historical sources accessible through technical visits to the Municipal History Museum of Cornelius Procopio, Natural History Museum of Cornelius Procopio and India Vanuire Historical and Pedagogical Museum, in Tupã, educational institutions such as the Rodolfo Wild School and Santa Mariana’s culture secretariat. Also, as a methodological referral, an extension course "Women of Santa Mariana - Formation, History and Memory" was organized to help constitute the corpus of analysis. From these data were organized the gestures of readings around the concepts of patriarchy, pioneering and colonization.